How emotions affect logical reasoning: evidence from experiments with mood-manipulated participants, spider phobics, and people with exam anxiety - Jung, Nadine; Wranke, Christina; Hamburger, Kai; Knauff, Markus (Frontiers in Psychology, 2014)
Recent experimental studies show that emotions can have a significant effect on the way we think, decide, and solve problems. This paper presents a series of four experiments on how emotions affect logical reasoning. In two experiments different groups of participants first had to pass a manipulated intelligence test. Their emotional state was altered by giving them feedback, that they performed excellent, poor or on average. Then they completed a set of logical inference problems (with if p, then q statements) either in a Wason selection task paradigm or problems from the logical propositional calculus. Problem content also had either a positive, negative or neutral emotional value. Results showed a clear effect of emotions on reasoning performance. Participants in negative mood performed worse than participants in positive mood, but both groups were outperformed by the neutral mood reasoners. Problem content also had an effect on reasoning performance. In a second set of experiments, participants with exam or spider phobia solved logical problems with contents that were related to their anxiety disorder (spiders or exams). Spider phobic participants’ performance was lowered by the spider-content, while exam anxious participants were not affected by the exam-related problem content. Overall, unlike some previous studies, no evidence was found that performance is improved when emotion and content are congruent. These results have consequences for cognitive reasoning research and also for cognitively oriented psychotherapy and the treatment of disorders like depression and anxiety.